INGN-225: a dendritic cell-based p53 vaccine (Ad.p53-DC) in small cell lung cancer: observed association between immune response and enhanced chemotherapy effect - Chiappori, Alberto A (2010)
IMPORTANCE OF THE FIELD: Novel approaches are needed for patients with small cell lung cancer (SCLC), as response after relapse is poor with standard therapies. p53 gene mutations often occur, resulting in tumoral protein overexpression and allowing for their recognition by p53-specific cytotoxic T cells. AREAS COVERED IN THIS REVIEW: We describe the characteristics and manufacturing of INGN-225, a p53-modified adenovirus-tranduced dendritic cell vaccine, and review available data, to understand INGN-225’s role in SCLC treatment. We discuss our pre-clinical, early Phase I/II, and ongoing randomized Phase II studies. WHAT THE READER WILL GAIN: INGN-225 was well tolerated (all toxicities ≤grade 2) in the Phase I/II trial (54 patients receiving at least 1 dose). Specific antip-53 immune response was positive in 18/43 (41.8%) patients, with overall post-INGN-225 response observed in 17/33 (51.5%) and immune response data available in 29 (14 positive, 15 negative). Post-INGN-225 response was observed in 11/14 (78.6%) and 5/15 (33%) patients with positive and negative immune responses, respectively. TAKE HOME MESSAGE: INGN-225 is safe, induces a significant immune response, and appears to sensitize SCLC to subsequent chemotherapy. Improvements in immune response induction and understanding the chemotherapy–immunotherapy synergism will determine INGN-225’s future role as an anticancer therapy.